Penataan Sarana Prasarana Pasar di Kawasan Perumahan Vila Mutiara Cikarang Tata Kota dan Daerah - Kerlima Hutagaol; Riza Fahlevi; Budi Harta Winata; Meliana Nur Evani (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
A market is a place where buying and selling transactions take place between sellers and buyers at a specific time and place. This definition encompasses several key elements: the presence of sellers, buyers, a specific place and time, and a transaction agreement. Such markets are also known as traditional markets. "Surprise" or "overflow" markets are markets that open suddenly and briefly. "Surprise" or "overflow" markets are increasingly common in various locations. There are many reasons why people enjoy shopping at these markets. One example is the very low prices, especially compared to shopping at supermarkets or malls. Over time, with the increasing demand for basic necessities, the "surprise" market, located along the road in the Vila Mutiara Cikarang housing complex, has also experienced gradual development. The number of traders and buyers has increased, the trading space has expanded, and transaction times have decreased. This "surprise" market is located along the road in the Vila Mutiara Cikarang housing complex, starting from the second block to the end of the road exiting the housing complex. The "surprise" market operates during peak hours, especially in the morning, when this time is not only for market activities but also for many activities such as going to work, school, and other activities.